2011
DOI: 10.1002/ejoc.201100291
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Reactions of Propargyl Esters with Vinyl Derivatives

Abstract: A gold-catalyzed olefin cyclopropanation reaction of propargyl esters with vinyl ester or vinyl sulfonamide derivatives was investigated for the synthesis of highly substituted cyclo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The mechanistic studies showedt hat the intramolecular CÀOb ond formation proceeded through au nique carboxy migration from an Au III organogold intermediate. [163][164][165][166][167] The CÀOc oupling product is formed through selectfluor-mediated fluorination/defluorinations equences.H owever,t he revised role of selectfluor proposed from the theoretical calculations is yet to be verified by experimental studies. [162] Contrary to the originally proposed mechanisms, calculations indicated that selectfluor does not oxidize Au I to Au III .…”
Section: Selectfluor As Asacrificial Oxidantina U I /Au Iii Catalysismentioning
confidence: 99%
“…The mechanistic studies showedt hat the intramolecular CÀOb ond formation proceeded through au nique carboxy migration from an Au III organogold intermediate. [163][164][165][166][167] The CÀOc oupling product is formed through selectfluor-mediated fluorination/defluorinations equences.H owever,t he revised role of selectfluor proposed from the theoretical calculations is yet to be verified by experimental studies. [162] Contrary to the originally proposed mechanisms, calculations indicated that selectfluor does not oxidize Au I to Au III .…”
Section: Selectfluor As Asacrificial Oxidantina U I /Au Iii Catalysismentioning
confidence: 99%
“…From the results of this and previous studies on goldcatalyzed reactions between propargyl esters and enol ether or enol esters, 11,15 product distribution depends mainly on the structure of the enols. Enol ethers may lead to formal [3+2] cycloaddition products, but enol esters produce primarily cyclopropanation products.…”
Section: Introductionmentioning
confidence: 90%
“…A similar cyclopropanation of vinyl esters has been reported by Fiksdahl, but the substrate was much simpler and a different Au catalyst was used. 15 In the presence of gold catalyst 2, propargyl ester 1 and vinyl ester 4 reacted smoothly at room temperature to afford the vinyl cyclopropane 7 in 75% yield, Scheme 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Most vinyl derivatives afforded the cyclopropanation products. In one case, both cyclopropane and cyclopentene products were observed and the cyclopropane could not be converted to the corresponding cyclopentene.…”
Section: Cycloadditions Involving Au-catalyzed 12-acyloxy Migratimentioning
confidence: 99%